PELATIHAN KERAJINAN KAWAT BULU DAN POT BOTOL BEKAS SEBAGAI EDUKASI LINGKUNGAN DAN PEMBERDAYAAN EKONOMI KREATIF DI BAGI HESSA PERLOMPONGAN - Oktaviana Nirmala Purba; Ansorrudin Ansorrudin; Zahrotun Wardah; Aisyah Dwia Ningsih; Putriyani Putriyani; Santry Alawyah (Smart Education, 2025)
Abstract: Wire craft and recycled bottle pot training activities were conducted to enhance the skills and environmental awareness of PKK women in Hessa Perlompongan Village. This program is part of the Community Service Program (PKM) by KKNT students of the Faculty of Teacher Training and Education, Asahan University, focusing on women’s empowerment through a recycling-based creative economy. The implementation stages included socialization, hands-on training, mentoring, and evaluation. The results showed a significant improvement in participants’ abilities to transform used materials into valuable products, with an average increase from 20% to over 90% after training. Participants also demonstrated high creativity and enthusiasm in producing crafts with market potential. This program not only fostered entrepreneurial spirit and economic independence but also raised awareness of responsible household waste management. Therefore, the training proved effective as an educational medium for promoting environmental awareness and creative economic empowerment within the community.Keywords: Recycled bottle, environmental education, recycling-based creative economy, pipe cleaner, PKK women empowerment. Abstrak: Kegiatan pelatihan kerajinan kawat bulu dan pot dari botol bekas dilaksanakan untukmeningkatkan keterampilan serta kesadaran lingkungan bagi ibu-ibu PKK Desa Hessa Perlompongan. Program ini merupakan bagian dari kegiatan PKM mahasiswa KKNT FKIP Universitas Asahan yang berfokus pada pemberdayaan Perempuan melalui ekonomi kreatif berbasis daur ulang. Metode pelaksanaan meliputi sosialisasi, pelatihan praktik, pendampingan dan evaluasi. Hasil kegiatan menunjukkan peningkatan signifikan pada keterampilan peserta dalam mengolah bahan bekas menjadi produk bernilai guna, dengan peningkatan kemampuan rata-rata dari 20% menjadi di atas 90% setelah pelatihan. Peserta juga menunjukkan kreativitas tinggi serta antusiasme dalam menciptakan karya kerajinan yang memiliki potensi nilai jual. Program ini tidak hanya menumbuhkan semangat kewirausahaan dan kemandirian ekonomi, tetapi juga menanamkan kesadaran akan pentingnya pengelolaan limbah rumah tangga secara bijak. Dengan demikian, pelatihan ini efektif sebagai sarana edukasi lingkungan dan pemberdayaan ekonomi kreatif bagi masyarakat desa. Kata Kunci: Botol bekas, edukasi lingkungan, ekonomi kreatif berbasis daur ulang, kawat bulu, pemberdayaan ibu PKK.